(untitled) - Passman, Roger (San Francisco, CA., 2007)
Teaching Writing in the Inclusive Classroom offers teachers in grades 6–12 everything they need to help all students develop basic writing skills, relate writing to real-life tasks, and explore writing as a creative and enjoyable practice. Filled with fifty engaging activities, this hands-on resource is an important and valuable tool that can supplement any teacher's approach to writing instruction. Teaching Writing in the Inclusive Classroom offers strategies based on the proven TIP Writing Process that is designed to individualize the writing process by focusing on the specific needs of each student within the classroom.
Keywords: English language,Composition ( Language arts ); Composition and exercises,Study and teaching